2014
DOI: 10.1088/0004-637x/781/2/70
|View full text |Cite
|
Sign up to set email alerts
|

THE JET AND ARC MOLECULAR CLOUDS TOWARD WESTERLUND 2, RCW 49, AND HESS J1023–575;12CO AND13CO (J= 2-1 andJ= 1-0) OBSERVATIONS WITH NANTEN2 AND MOPRA TELESCOPE

Abstract: We have made new CO observations of two molecular clouds, which we call "jet" and "arc" clouds, toward the stellar cluster Westerlund 2 and the TeV γ -ray source HESS J1023−575. The jet cloud shows a linear structure from the position of Westerlund 2 on the east. In addition, we have found a new counter jet cloud on the west. The arc cloud shows a crescent shape in the west of HESS J1023−575. A sign of star formation is found at the edge of the jet cloud and gives a constraint on the age of the jet cloud to be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 83 publications
3
24
0
Order By: Relevance
“…The studies of the CO emission spectrum in combination with the 21 cm absorption spectrum by Dame (2007) suggest that Wd2 must be located in between two molecular clouds. Wd2 was studied in more detail by Furukawa et al (2009Furukawa et al ( , 2014 and Ohama et al (2010) using the NAN-TEN 2 4m submillimeter/millimeter telescope (from the NANTEN CO Galactic Plane Survey, Mizuno & Fukui 2004) in combination with Spitzer data. They detected three different CO clouds with 3 different velocities (16, 4, and −4 km s −1 , relative to the local standard of rest (LSR), see Fig.…”
Section: The 12 Co and 13 Co Transition Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies of the CO emission spectrum in combination with the 21 cm absorption spectrum by Dame (2007) suggest that Wd2 must be located in between two molecular clouds. Wd2 was studied in more detail by Furukawa et al (2009Furukawa et al ( , 2014 and Ohama et al (2010) using the NAN-TEN 2 4m submillimeter/millimeter telescope (from the NANTEN CO Galactic Plane Survey, Mizuno & Fukui 2004) in combination with Spitzer data. They detected three different CO clouds with 3 different velocities (16, 4, and −4 km s −1 , relative to the local standard of rest (LSR), see Fig.…”
Section: The 12 Co and 13 Co Transition Linesmentioning
confidence: 99%
“…Using the rotation curve of Brand & Blitz (1993), Furukawa et al (2009) obtained kinematic distances of 6.5, 5.2, and 4.0 kpc for the 16, 4, and −4 km s −1 clouds, respectively. Furukawa et al (2009Furukawa et al ( , 2014 and Ohama et al (2010) also suggested that the creation of the RCW 49 region, with the Wd2 cluster as its central ionizing cluster, was induced by a cloud-cloud collision of two of these observed molecular clouds. This collision may have caused the formation of the spatially uniformly distributed low-mass PMS stars that we see in our HST data.…”
Section: The 12 Co and 13 Co Transition Linesmentioning
confidence: 99%
“…Let us compare our results with CO observations (Furukawa et al 2014). The velocity dispersion of the molecular clouds formed by the jet-cloud interaction depends on the jet speed.…”
Section: Summary and Discussionmentioning
confidence: 70%
“…HESS J1023-575 is observed both at the high energy band (above 2.5 TeV) and the low energy band (0.7 − 2.5 TeV). The cooling by the pp-interaction and diffusion time scales of the relativistic particles are estimated to be about 5 × 10 6 yr and 2 × 10 4 yr, respectively, by Furukawa et al (2014). If the arc and the jet clouds and TeV γ-ray source are produced by a single object, a supernova remnant or a pulsar wind nebulae is not likely as the origin for TeV γ-ray source since the diffusion time scale of the relativistic particles is shorter than the age of the arc and jet clouds (∼ Myr).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The reduced maps (FITS files) are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/617/A77 in many environments, for instance, in photodissociation regions (PDRs), protoplanetary disks, young stellar objects (YSOs; Martín et al 2009;Sturm et al 2010;Furukawa et al 2014), and different extragalactic environments, such as low surface brightness galaxies, high-redshift galaxies, and ultra-luminous infrared galaxies (ULIRGs;O'Neil et al 2000;Schleicher et al 2010;Papadopoulos et al 2010).…”
Section: Introductionmentioning
confidence: 99%